Reactive Oxygen Species and Inhibitors of Inflammatory Enzymes, NADPH Oxidase, and iNOS in Experimental Models of Parkinson's Disease - Sushruta Koppula; Hemant Kumar; In Su Kim; Dong-Kug Choi (Hindawi Limited, 2012)
Reactive oxygen species (ROSs) are emerging as important players in the etiology of neurodegenerative disorders including Parkinson's disease (PD). Out of several ROS-generating systems, the inflammatory enzymes nicotinamide adenine dinucleotide phosphate (NADPH) oxidase and inducible nitric oxide synthase (iNOS) were believed to play major roles. Mounting evidence suggests that activation of NADPH oxidase and the expression of iNOS are directly linked to the generation of highly reactive ROS which affects various cellular components and preferentially damage midbrain dopaminergic neurons in PD. Therefore, appropriate management or inhibition of ROS generated by these enzymes may represent a therapeutic target to reduce neuronal degeneration seen in PD. Here, we have summarized recently developed agents and patents claimed as inhibitors of NADPH oxidase and iNOS enzymes in experimental models of PD.